The everyday blacksmith : learn to forge 55 simple projects you'll use every day - Wicks, Nicholas (Beverly, MA : Quarry Books, 2019)
"The Everyday Blacksmith empowers hobbyist blacksmiths to make simple, practical projects for everyday use"--
Tools and techniques -- Setting up shop -- Finishes -- Projects to start -- Projects -- Tools -- Around the home -- Kitchen and bath -- Cooking -- Outdoor -- Jewelry -- Hardware.
Includes bibliographical references and index.
Keywords: Blacksmithing -- Amateurs' manuals